Understanding the lived experiences of cyberbullying and coping strategies among social media influencers on social media - Ab Rashid, Faridah Hanem (2022)
The shift from physical reality to a virtual counterpart indicates the unprecedented interactivity and prevalence of social media usage where social media influencers (SMIs) could develop a strong rapport with their followers. The SMIs are followed by passionate and participative individuals with high regard for their perspectives and detractors. Notwithstanding, SMIs are susceptible to cyberbullying despite being notable brand endorsers or influential opinion leaders. This qualitative transcendental phenomenological research (i) examined 10 SMIs’ lived experiences of being cyberbullied on social media and (ii) strived to comprehend the implications of cyberbullying on victims (SMIs) together with their coping mechanisms. The adverse effects of cyberbullying could be attributed to broader social media audiences who virtually reflect meanness and cruelty, which could lead to suicides and long-term depression. Semi-structured and face-to-face online interviews with open-ended questions were implemented in this study to elicit in-depth informant experiences. Underpinning theories involving the Social Cognitive Theory (self-efficacy and self-regulation) and Transactional Model of Stress and Coping were utilised as empirical guidelines. The study data, which were evaluated through Moustakas’s modified Stevick-Colaizzi-Keen phenomenological analysis method, led to the identification of nine themes: (i) associated with cyberbullying activities; (ii) instantaneous famous but negatively portrayed; (iii) online media and online portals used for sensational news; (iv) less personal information posting on social media; (v) post pleasant and enlightening content; (vi) desire to bring awareness; (vii) problem-focused coping strategies; (viii) emotion-focused coping strategies; (ix) cyber coping strategies. Resultantly, the informants portrayed high levels of self-worth through self-descriptions, particularly in managing cyberbullying incidents. The informants were also unaware that their social media content inevitably instigated cyberbullying. In this vein, cyberbullying typically occurs through online portals and news platforms. The current research could facilitate communication and media education practitioners, social media and anti- cyberbullying authorities, and relevant policymakers to comprehend how cyberbullying impacts social media contexts and provides the victims with optimal countermeasures to protect and resolve such incidents. Summarily, this research has bridged the existing literature gap for a holistic comprehension of actual cyberbullying experiences on social media posting and optimal countermeasures among public figures, such as SMIs.